1977
DOI: 10.1007/bf00235503
|View full text |Cite
|
Sign up to set email alerts
|

Tetanus toxin induced actions on spinal Renshaw cells and Ia-inhibitory interneurones during development of local tetanus in the cat

Abstract: In anaesthetized cats the activities of Renshaw cells (RCs) and Ia-inhibitory interneurones (IaINs) were recorded during the accumulation of tetanus toxin in the spinal cord following injection into the gastrocnemius muscle. The early response of the RCs increased during the period of development of local tetanus. With some cells there was a subsequent decrease in the early response in later periods of the observation time (16-44 hrs after intramuscular injection). The effects on the spontaneous activity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 34 publications
1
14
0
1
Order By: Relevance
“…TeTx holotoxin induces spastic paralysis due to LC activity in inhibitory spinal interneurons 30,31 or epilepsy due to its activity in hippocampus. 32 Unlike the effect of TeTx holotoxin, adenoviral LC gene delivery induced a flaccid paralysis secondary to the neuromuscular blockade.…”
Section: Light Chain Gene-based Synaptic Inhibition Q Teng Et Almentioning
confidence: 99%
“…TeTx holotoxin induces spastic paralysis due to LC activity in inhibitory spinal interneurons 30,31 or epilepsy due to its activity in hippocampus. 32 Unlike the effect of TeTx holotoxin, adenoviral LC gene delivery induced a flaccid paralysis secondary to the neuromuscular blockade.…”
Section: Light Chain Gene-based Synaptic Inhibition Q Teng Et Almentioning
confidence: 99%
“…Tetanus holotoxin causes spastic paralysis through a primary action on inhibitory spinal interneurons. 16,17 Thus, initial experiments in the spinal cord suggested that LC's activity could be redirected through neuronal expression. In the present experiment, confocal microscopy and Western blots revealed reduced VAMP-1 levels in brain tissue expressing LC, supporting the hypothesis that LC is capable of neural inhibition in structures that are normally unaffected by the holotoxin.…”
Section: Discussionmentioning
confidence: 99%
“…Produced by anaerobic Clostridium tetani germinating in infected wounds, TeTx released via autolysis of the bacteria spreads into the circulation until it eventually reaches and binds with high affinity to peripheral nerve endings. Upon internalization, it migrates by fast intra-axonal transport to spinal cord and brain stem; there it blocks inhibitory transmission, causing spastic paralysis and death if untreated (Benecke et al 1977;Fishman 2009). Synthesized as a *150 k single-chain protein, TeTx is post-translationally cleaved into a di-chain (DC) composed of a *100 k heavy chain (HC) and *50 k light chain (LC) protease linked via a di-sulfide bridge and non-covalent bonds (Craven and Dawson 1973;Rossetto et al 2001;Turton et al 2002).…”
Section: Introductionmentioning
confidence: 97%